One stage bilateral endoscopic sympathectomy under local anesthesia: Is a valid, and safe procedure for treatment of palmer hyperhidrosis? - Awad Mohamed; Elzeftawy Awny; Mansour Salah; Elshelfa Wael (Journal of Minimal Access Surgery, 2010)
Objective : Thoracoscopic sympathetic surgery is currently the best treatment for hyperhidrosis, and the success rate is quite high, but poor emphasis has been given to the type of anaesthesia and its application through either one or two stages of surgery. This study has evaluated the operative and postoperative results of one-stage bilateral thoracoscopic sympathectomy under local anaesthesia. Materials and Methods : From 2003 to 2007, n=14 patients with hyperhidrosis of the upper limbs [4 females and 10 males] with a mean age of 28±2.11 year [range 26-44] were included. They were operated on by means of bilateral ETS under local anaesthesia. The mean follow-up was 1.5 years (range 13-24 months). Results : No operative mortality was recorded. The mean operating room time for the whole bilateral procedure under was 73. 5±14.5 range [60 -120] min most of the patients were discharged the same day after a chest roentgenogram except, only two patients with gustatory sweating one recurrent sweating in the patient who had previously axillary hyperhidrosis. Also among them two patients (20%) experienced a minimal pneumothorax that required no treatment. Postoperative quality of life and satisfaction were excellent and cost was significantly reduced. Conclusions : Bilateral thoracoscopic sympathectomy for palmar hyperhidrosis could be safely and effectively performed in patients refusing GA regarding cost and satisfaction.